Mesurer le niveau de stress d’enfants à leur domicile (Marseille) : Mise au point méthodologique - Valérie Niel-Bernard; Hélène Pagezy; Pierre Darlu (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The stress levels of 40 Senegalese migrant children were studied by measuring the level of cortisol, adrenalin, noradrenalin, and dopamine in their 24-hour urinary excretion. The choice and the adaptation of methods necessary for carrying out a study in the family environment rather than under hospital conditions are specified. Urinary cortisol is taken as a good indicator of a psychosocial stress over a long period. The measurement of stress hormones should be expressed in relation to age, weight, height, body surface and body mass index (BMI). The last two indexes are enough to express cortisol independently of age and body shape. However, while pediatricians tend to use body surface (calculated from Gehan and George’s formulas), seldom applying the exact formula related to age, anthropobiogists mostly prefer to use BMI. A suitable standardization of the results is needed, particularly when the objective is to measure children’s stress under “normal” conditions, that is at their family home.